The Role of Evaporitic-Shale Sediment Packages in the Localisation of Copper-Gold Deposits: Copper Canyon Area, Cloncurry - J I Stewart (The Australasian Institute of Mining and Metallurgy, 1994)
The Copper Canyon deposits, occur in proximity to the regionally distinctive formational boundary between the Staveley Formation and Marimo Shale. The mineralisation here is associated with breccias, veins, and alteration zones near the base of the Marimo Shale unit and in the underlying evaporitic dolomite-dololutite dominant Staveley Formation. The Marimo Shale unit, in its basal 60 metres, is highly carbonaceous and hosts ubiquitous but minor diagenetic (?) copper-pyrite, and on occasion, extensive albite-microcline alteration centres, pyritic (cobaltiferous)-quartz veins, and microcline-quartz_+plagioclase veins or veinlet arrays. The most significant mineralisation, such as at the Greenrnount prospect, consists of a shallowly dipping package of alteration zones overprinted by multiple generations of pink-orange microcline-quartz-chalcopyrite-pyrite-(arsenopyrite) and albite-calcite- phlogopite veins. Accessory mineralogies in most of these mineralisation styles consist of tourmaline, monazite, rutile, and apatite. Chalcopyrite (and secondary chalcocite) and gold are associated with each generation of alteration but are best developed in the later stages of veining. In the underlying Staveley Formation, which is a conformable transition between the Corella Formation limestones and the Marimo Shale, chalcopyrite (cobaltiferous)-pyrite mineralisation occurs as disseminations in pre- and syntectonic breccias, and with disaggregated silica pseudomorphs (after thinly bedded evaporitic sulphate beds) and associated dolomitised limestone-calcilutite. Although this mineralisation may be partly diagenetic in origin the 200 in thick evaporitic packages are also host to a locally widespread (2 to 4 km long and 200 to >500 metres wide) and pervasive 'redrock' styled microcline-dolomite¦hematite alteration. Within this gross alteration package there also seems to be a consistent association with narrow (10 to 100 metres wide), linear (stratabound) semi-massive magnetite-hematite-microcline and quartz-chalcedony replacement zones. Like much of the nearby Corella Formation the Staveley Formation, under the Marimo Shale, has undergone dissolution, paleo-solution karsting (breccias) and tectonic brecciation such that the precursor lithological details have been progressively obliterated. The post-diagenetic to post-tectonic fluid pathway development and metasomatic alteration history of this important lithostructural package of rocks has been traced from preliminary studies only. The ability to do so is largely due to the absence of significant regional and contact metamorphic overprinting, and the local preservation of precursor sediment profiles. It is proposed that both the base of the Marimo Shale and parts of the underlying evaporitic-limestone-dololutite have acted as conformable fluid pathways for hydrothermal and (perhaps) diagenetically derived, Cu-Au-(¦Co ¦As) K-Na-Ti-REE bearing, fluids and brines.